1971
DOI: 10.1007/bf03025690
|View full text |Cite
|
Sign up to set email alerts
|

Forane (Compound 469): 2. Biochemical effects of repeated administration to animals, response to bleeding, and compatibility with epinephrine

Abstract: Trm EXPERIMENTS ltEPORTED here were designed to reveal some biochemical effects which might be produced by the repeated inhalation of Forane by dogs and monkeys, and to compare its influence on the cardiac irritability of dogs with that of other halogenated anaesthetics. METHODS Biochemical Effects in DogsTwo groups of five mature, pedigreed, female beagles were used, having a mean body weight of 10.6 kg. Each of the dogs in one of these groups had an open liver biopsy taken, under thiopentone anaesthesia, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…While enflurane has been reported by some 11' 12 to "sensitize" the myocardium, a comparative evaluation of enflurane and methoxyflurane in beagles by Byles et al 13 found cardiac irritability with both anaesthetics to be similar and significantly less ,as compared with halothane. Similar observations have been made in unpremedicated goats anaesthetized with these anaesthetics.…”
Section: Discussionmentioning
confidence: 95%
“…While enflurane has been reported by some 11' 12 to "sensitize" the myocardium, a comparative evaluation of enflurane and methoxyflurane in beagles by Byles et al 13 found cardiac irritability with both anaesthetics to be similar and significantly less ,as compared with halothane. Similar observations have been made in unpremedicated goats anaesthetized with these anaesthetics.…”
Section: Discussionmentioning
confidence: 95%
“…[19] In the prospective human study of repeated sevoflurane anesthesia, the multiple administration of sevoflurane anesthesia was not related to adverse effects of liver and renal damage. [17] Repeated isoflurane anesthesia did not produce liver and renal damage in an animal study,[20] while Brunt et al . reported a case with liver damage by repeated isoflurane anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Isoflurane does not need to be stabilized with preservatives and is nonflammable over all ranges of application. Prolonged and/or repetitive isoflurane anesthesia does not cause hepatorenal damage even when administered to animals for up to 35 consecutive days (Byles et al, 1971). No hepatic necrosis is seen with isoflurane administra-tion even under conditions where other anesthetics do cause hepatic necrosis (Harper et al, 1981).…”
mentioning
confidence: 99%